Makna Performa POLRI Dalam Membentuk Budaya Organisasi - Asriyani Sagiyanto (Universitas Bina Sarana Informatika, 2016)
Cultural organizations often come to the surface to be studied well even amongpractitioners and academics . One of the current organizational culture has always beenthe public spotlight is organizational culture of government agencies such as theIndonesian National Police. Lots of police performance that can be understood by thepeople that have to be considered in the organizational culture that agency. With theperformance that is within the police, we can examine and construct meaning , whetherseen from the performance within an organizational culture rituals , socialization ,politics and enculturation , which has now turned into a culture of police organizations .Construction of meaning police expected performance body DAPT understood by thepublic or the members in the organization, so that organizational culture can beperceived negatively by the public to be repaired a positive organizational culture . Thusthe performance of the Police will also turn out to be positive.